Senderos de los Andes (2020)
This mixed-use project between housing, commerce and industry is in charge of densifying a medium-sized lot located in the Barrio los Andes de Bogotá. This consists of three parts, the first corresponds to a multi-family housing which is distributed in 8 towers within which apartments of 2 types stand out, all of which are duplexes. The second part of the project is a textile recycling factory which operates in the basement and first floor of the project, in which it is expected to recycle around 5 tons of fabric per month. The third part of the project is made up of the public space and its shops, where in some shops the fabrics already recycled by the factory will be sold.